The category of relation in Benedykt Hesse - Stanek, Maciej (Folia Philosophica, 2012)
The paper addresses Benedykt Hesse’s attempt to determine the category of relation through definitions and a list of its characteristics. I emphasise that the definitions were insufficient tool for philosophers of the Middle Ages and for this reason they used lists of their characteristics as well. In revived, 15th-century Cracow University Jean Buridan’s terministic concept was critically accepted and used for development of a new scientific formation - via communis - which tried to make an agreement between opposite philosophical standpoints, namely those of nominalism and realism, and hence invoking some historical background in the paper was necessary. Quotations from Benedykt Hesse were taken from his commentary on Categories from manuscripts of signatures BJ 2037, BJ 2043 and BJ 2455, as well as from anonymous commentary by one of Hesse’s students preserved in BJ 1900 manuscript.